Cinematic Chronology: Exploring the Signs and Symbols of Time in “Atonement” - Prabowo, Bayu Ade (LPPM Universitas Bumigora Mataram, 2024)
This study investigates the representation of time in Joe Wright’s film ’Atonement’ (2007), exploring the complex ways cinema can portray temporal experiences. While time manipulation in the film has been widely studied, ’Atonement’ offers a unique case study in its intricate layering of temporal elements. The research aims to analyze how various cinematic techniques in ’Atonement’ contribute to its representation of time and memory. Employing a descriptive-qualitative method with semiotic analysis, this study examines five key aspects: non-linear narrative structure, dual perspective and metafiction, the long take in the Dunkirk scene, representation of historical periods, and the use of sound and music. The findings reveal that ’Atonement’ utilizes a sophisticated interplay of narrative, visual, and auditory elements to create a multifaceted temporal experience. The film’s non-linear structure, meticulous recreation of historical periods, and innovative sound design challenge traditional notions of cinematic time. This innovative approach effectively addresses the research aim by demonstrating how ’Atonement’ uses various cinematic techniques to construct a complex temporal narrative. This research contributes to understanding how cinema can represent complex temporal narratives, offering insights for film studies and narrative theory.